A geographic cross-layer routing adapted for disaster relief operations in wireless sensor networks. (November 2017) - Niroumand, Zahra; Aghdasi, Hadi S.
Highlights: Routing problem in WSNs for disaster relief operations is tackled by a cross-layer geographic method named geographic cross-layer routing adapted for disaster (GCRAD) relief operations . GCRAD suggests a criterion named potential relay number (PRN) for decreasing the probability of collision as much as possible. GCRAD removes the undesirable imposed priority by jointly affecting the relay node selection criteria such as distance to the sink and queue status. GCRAD outperforms state-of-the-art methods in terms of end-to-end delay, energy consumption and achieves acceptable delivery ratio. Abstract: Wireless Sensor Networks (WSNs) have been studied for various applications, especially for facilitating relief operations in disasters such as earthquake and fire. In this paper, we propose a new geographic cross-layer routing method in WSNs called geographic cross-layer routing adapted for disaster (GCRAD) relief operations. GCRAD integrates MAC and routing using a handshake mechanism for relay selection and considers node's queue status, distance to the sink, and the number of potential relay nodes as the relay selection criteria. GCRAD eliminates the ineffective transmissions and shortens the handshake mechanism by affecting these criteria in a single step (all of them concurrently) and also, decreases the collision probability as much as possible. Through ns2-based simulations, we show that GCRAD significantly achieves lower end-to-end delay, lower energy consumption, and acceptable delivery ratio in comparison with the state-of-the-art geographic cross-layer routing methods, especially in high traffics, which is the main characteristic of disasters.